ATMAN SEBAGAI SAT GURU DALAM AJARAN JNANA BUDA SIWA PADA ASHRAM LEMBAH BHAYAM - Parbasana, Nyoman; D.E., Relin; Wiguna, I Made Arsa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This research departs from the problem of how to achieve the existence of Atman as a Sat Guru in the Jnana Buda Shiva teachings taught at the Ashram Lembah Bhayam in Bababahan village, Penebel subdistrict, Tabanan district. Atman as Sat Guru is Atman as a life guide that emerges from within oneself through the deepest conscience as the most important goal of life based on Hinduism because Atman is the all-knowing within oneself. Achieving Atman's guidance is the path to achieving moksartam jagadhita ya ca iti darmah”, which is a universal path and has various variations, especially through the path of tapa bharata yoga samadhi. The formulation of the problem raised: (1) What is the existence of Atman as a Sat Guru in the Jnana Buda Shiva teachings taught at the Ashram Lembah Bhayam in Babahan Village, Penebel District, Tabanan Regency? (2) What are the Hindu theological aspects of the concept of Atman as the Sat Guru in the Jnana Buda Shiva teachings at the Ashram Lembah Bhayam in Babahan Village, Penebel District, Tabanan Regency? (3) What are the implications of the application of Atman as a Sat Guru in the Jnana Buda Shiva teachings for the Bhakti at the Ashram Lembah Bhayam in Babahan Village, Penebel District, Tabanan Regency? Hindu theology taught in the Jnana Buda Shiva teachings is mainly about the Tri Purusa teachings which consist of God as: Parama Shiva, Sasdha Shiva and Shivatman. The results of this research are that Bhakti as Sisya of Maha Guru Sri Jaya Nara in the initial stages are required: (1) Sisya candidates are required to train themselves and face for at least one year in order to establish themselves to become Bhakti of Ashram Lembah Bhayam. After that, you can receive Upanayana Samkara purification. And students who can receive Upanayana Samkara must also be 14 years or older. (2) You must worship and meditate at least once a day, develop love for fellow human beings, cultivate a sense of peace and sincerity in devotion. (3) Devoted to parents, guiding teachers and diligently cultivating knowledge in the soul. (4) Obediently implementing the teachings of Guru Padesa Maha Guru Sri Jaya Nara in order to become Para Bhakti of Ashram Lembah Bhayam with its glory. (5) Ready to accept sadhana as a process of getting to know Atman as Sat Guru in his samadhi or in whatever conditions his Atman desires. (6) Ready to serve the Indonesian archipelago and the nation, fight and pray for the sake of world peace. This provision is always reminded to the Ashram Lembah Bhayam devotees so that the devotees are always aware and sincerely accept the soul of mukti as an implication of knowing Atman as the Sat Guru.